1997
DOI: 10.1093/emboj/16.9.2197
|View full text |Cite
|
Sign up to set email alerts
|

Negatively charged amino acid residues play an active role in orienting the Sec-independent Pf3 coat protein in theEscherichia coliinner membrane

Abstract: The coat protein of Pseudomonas aeruginosa phage Pf3 is transiently inserted into the bacterial inner membrane with a single transmembrane anchor sequence in the NoutCin orientation. The N‐terminal sequence immediately flanking the membrane anchor contains one negatively charged residue, whereas the C‐terminal hydrophilic segment has two positively charged residues. To investigate how the orientation of this protein is achieved, the three flanking charged amino acid residues were altered. Membrane insertion wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 33 publications
(57 reference statements)
4
82
2
Order By: Relevance
“…coat protein of Pseudomonas aeruginosa phage Pf3 in E. coli, where it was shown that, when both termini carried a negative net charge, the Pf3 protein was able to insert either the N or the C terminus into membranes, leading to a 50%/50% mixed topology (26). However, in this study, both N-and C termini of the Pf3 protein were short.…”
Section: Discussioncontrasting
confidence: 53%
“…coat protein of Pseudomonas aeruginosa phage Pf3 in E. coli, where it was shown that, when both termini carried a negative net charge, the Pf3 protein was able to insert either the N or the C terminus into membranes, leading to a 50%/50% mixed topology (26). However, in this study, both N-and C termini of the Pf3 protein were short.…”
Section: Discussioncontrasting
confidence: 53%
“…the first step is targeting of Pf3 coat protein to the membrane, the second step is partitioning of the Pf3 coat hydrophobic domain into the membrane lipid bilayer, and the final step is the formation of a transmembrane helix with concomitant membrane translocation of the amino-terminal region (23). In the third step, the proton motive force (pmf) is required for the electrophoretic transfer of the amino-terminal tail, which contains two negatively charged amino acid residues (33). Our data obtained by photocrosslinking suggests that YidC functions at the stage of membrane insertion, which might be the membrane partitioning step (the second step) or the orientation step (the third step), to form the transmembrane form of the protein.…”
Section: Yidcmentioning
confidence: 99%
“…This export process resembles the bacterial N-tail export mechanism of the M13 procoat protein; it depends on the membrane potential and an Oxa1p homologue, YidC (17,27). The N terminus of Pf3 coat protein is exported in a membrane potential-dependent manner (25). Therefore, we examined whether the export of the N terminus of T7-Su8 depends on the membrane potential and/or ATP.…”
Section: Insertion Of T7-su8 Across the Membrane Depends On Thementioning
confidence: 99%
“…The M13 procoat protein is synthesized with a cleavable signal peptide and spans the membrane once with the processed N terminus exposed to the periplasm and the C terminus remaining in the cytoplasm (18 -24). The Pf3 coat protein is synthesized without a cleavable signal sequence and inserts into the membrane once, exposing the N-terminal segment to the periplasm and the C-terminal segment to the cytoplasm (25,26). In contrast to the predicted direct insertion mechanism, Samuelson et al (27) demonstrated that insertion of the M13 procoat protein across the membrane depends on a Oxa1p homologue, YidC.…”
mentioning
confidence: 99%